2021
DOI: 10.1021/acs.inorgchem.1c03021
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Transformation between Cs3Cu2I5 and CsCu2I3 Perovskite Derivatives and Its Anticounterfeiting Application

Abstract: Lead halide perovskites have promising values in photoelectronic and photovoltaic applications, but the toxicity of lead is a hard barrier. Copper halide perovskite derivatives (CHPDs), as a lead-free substitution of lead halide perovskites, also exhibit excellent photoelectric properties. Here, we present a facile one-step route for the synthesis of blue-emissive Cs3Cu2I5 (emission at 440 nm) and yellow-emissive CsCu2I3 (emission at 552 nm) CHPDs in ethanol at room temperature. Triggered by ethanol or CsI, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…To date, different synthetic approaches have been developed to prepare Cs–Cu–I perovskites, such as colloidal chemical methods, antisolvent strategy, and mechanical grinding methods . The rapid progress made in the synthesis of Cs–Cu–I perovskites drove the development of their applications in light-emitting diodes, photodetectors, anticounterfeiting, and so on. For example, researchers demonstrated that the reversible conversion between blue-emitting Cs 3 Cu 2 I 5 and yellow-emitting CsCu 2 I 3 through exposing or removing water exhibited excellent stability in the anticounterfeiting applications. , Yet, to date, few works have been reported on the relationship between luminescence tuning and phase transition of Cs–Cu–I perovskites on the nanoscale.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, different synthetic approaches have been developed to prepare Cs–Cu–I perovskites, such as colloidal chemical methods, antisolvent strategy, and mechanical grinding methods . The rapid progress made in the synthesis of Cs–Cu–I perovskites drove the development of their applications in light-emitting diodes, photodetectors, anticounterfeiting, and so on. For example, researchers demonstrated that the reversible conversion between blue-emitting Cs 3 Cu 2 I 5 and yellow-emitting CsCu 2 I 3 through exposing or removing water exhibited excellent stability in the anticounterfeiting applications. , Yet, to date, few works have been reported on the relationship between luminescence tuning and phase transition of Cs–Cu–I perovskites on the nanoscale.…”
mentioning
confidence: 99%
“…27−31 For example, researchers demonstrated that the reversible conversion between blue-emitting Cs 3 Cu 2 I 5 and yellow-emitting CsCu 2 I 3 through exposing or removing water exhibited excellent stability in the anticounterfeiting applications. 32,33 Yet, to date, few works have been reported on the relationship between luminescence tuning and phase transition of Cs−Cu−I perovskites on the nanoscale.…”
mentioning
confidence: 99%
“…S2(a)). Generally, CsI is dissolved from Cs 3 Cu 2 I 5 in the presence of moisture due to the high solubility of CsI in water, which leads to the formation of yellow-emissive CsCu 2 I 3 product within several minutes [10,23]. However, the encapsulated Cs 3 Cu 2 I 5 within PS bers can effectively prevent the extraction of CsI and maintain long-term stability by protecting water e ciently.…”
Section: Morphology and Structural Characterization Of Ipncsmentioning
confidence: 99%
“…To address this issue, it is necessary to develop high stability, eco-friendly broadband emission materials. Recently, many types of lead-free perovskites have been studied to replace toxic metallic lead with other non-toxic metals, such as tin halide (CsSnBr 3 , Cs 4 SnBr 6 ) [6, 7], bismuth halide (Cs 3 Bi 2 Br 9 ) [8], indium halide (Cs 2 InBr 5 ) [9], and copper halide (Cs 3 Cu 2 I 5 , CsCu 2 I 3 ) [10,11] based perovskites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation